European Bank Performance Beyond Country Borders: What Really Matters? * - Lozano-Vivas, Ana; Pastor, Jesús T.; Hasan, Iftekhar (Review of Finance, 2001)
Abstract The paper analyzes bank performance in the context of the integrated European Union market and its member countries. First, the paper investigates the technical efficiency of banks in each country sample using a Data Envelopment Analysis (DEA) model incorporating only banking variables. Then, a second DEA model is defined incorporating environmental factors together with banking variables in order to standardize the country-specific environmental conditions. Based on these models, the paper systematically analyzes the efficiency position for each of the European banking industry if average banks decide to operate in any other country. The results indicate that adverse (advantageous) environmental conditions are a positive (negative) factor for the home banking industry and being technically efficient appears to be a significant deterrence to foreign competition.